Physalis angulata L. (Solanaceae) - A new angiospermic record for Bangladesh (Bangladesh Journal of Botany, 2008)
Physalis angulata L., an annual herb, belonging to the family Solanaceae, has been described and illustrated as a new record for Bangladesh. Key words: Physalis angulata, New record, Bangladesh doi:10.3329/bjb.v37i2.1731 Bangladesh J. Bot. 37(2): 195-198, 2008 (December)